2017
DOI: 10.1021/acs.iecr.7b03746
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrothermal Liquefaction of Microalgae for Bio-oil Production over Silylated SBA-15 with High Hydrothermal Stability

Abstract: This paper mainly describes the application of silylated SBA-15 with high hydrothermal stability in catalytic hydrothermal liquefaction (HTL) of Dunaliella (D.) tertiolecta to produce bio-oil. The results indicated that selection of silylation reagent species contributes to improve hydrothermal stability of SBA-15 at 613 K through substituting hydroxyl group on SBA-15 surface. The grafting of silane on SBA-15 had an impact on pore size, wall thickness, specific surface area, pore volume, and other structure ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In Process Intensification , Hong Li et al studied the vapor–liquid equilibrium and economic evaluation in reversible reaction-assisted intensification process for separating the azeotropic mixture of ethanediol and 1,2-butanediol, Zhang et al reported a facile preparation of α-calcium sulfate hemihydrate with low aspect ratio using high-gravity reactive precipitation, combined with a salt solution method at atmospheric pressure. In Bioconversion , Qisong Lin et al described catalytic hydrothermal liquefaction (HTL) of microalgae for bio-oil production over silylated SBA-15 with high hydrothermal stability and Xiaochen Liu et al reported the biosynthesis of glycyrrhetinic acid-3-O-monoglucose, using glycosyltransferase UGT73C11 from Barbarea vulgaris . In Chemical Product Engineering , Pu et al reviewed the colloidal synthesis of semiconductor quantum dots toward large-scale production, Xiejun Huang et al investigated the ZnO nanoparticle applications in fabrication of ultrahigh content and stable polymer/ZnO nanoparticle nanocomposite film with excellent optical properties, and Kunhong Wu et al developed thermally reversible cross-linkers to facilitate the improved reprocessability of poly­(butyl methanol methacrylate) rubber with excellent thermal and mechanical properties.…”
mentioning
confidence: 99%
“…In Process Intensification , Hong Li et al studied the vapor–liquid equilibrium and economic evaluation in reversible reaction-assisted intensification process for separating the azeotropic mixture of ethanediol and 1,2-butanediol, Zhang et al reported a facile preparation of α-calcium sulfate hemihydrate with low aspect ratio using high-gravity reactive precipitation, combined with a salt solution method at atmospheric pressure. In Bioconversion , Qisong Lin et al described catalytic hydrothermal liquefaction (HTL) of microalgae for bio-oil production over silylated SBA-15 with high hydrothermal stability and Xiaochen Liu et al reported the biosynthesis of glycyrrhetinic acid-3-O-monoglucose, using glycosyltransferase UGT73C11 from Barbarea vulgaris . In Chemical Product Engineering , Pu et al reviewed the colloidal synthesis of semiconductor quantum dots toward large-scale production, Xiejun Huang et al investigated the ZnO nanoparticle applications in fabrication of ultrahigh content and stable polymer/ZnO nanoparticle nanocomposite film with excellent optical properties, and Kunhong Wu et al developed thermally reversible cross-linkers to facilitate the improved reprocessability of poly­(butyl methanol methacrylate) rubber with excellent thermal and mechanical properties.…”
mentioning
confidence: 99%